Role of NH3 Annealing Treatment in Improving SeN Layer on GaAs Substrate Using Electron Beam Evaporator - Alvin, Y. S. M.; Zainal, N.; Hassan, Z. (2015)
In this work, the growth of scandium nitride (SeN) on gallium arsenide (GaAs) substrate is demonstrated using electron beam (e-beam) evaporator with successive annealing in ammonia (NHJ) ambient. As observed in field effect scanning electron microscopy (FE-SEM), the surface morphology of the SeN layer was started to transform from rice grains-like structure to rock salt grains-like structure by increasing the temperature from 750 oc to 900 °C. The rock salt grains-like structure is similar to high quality SeN, as reported in literature. However, the surface degraded with the presence of voids at 980 °C. The existence of SeN bond was confirmed by x-ray photospectroscopy (XPS) measurement. The photoluminescence (PL) of near-to-band-edge SeN peak was observed in all samples. Furthermore, the SeN peaks in Raman spectrum were obvious when the sample was annealed above 850 °C. Based on the evidences, the growth of SeN using the above techniques was successful, with the annealing temperature above 850 °C.